An examination of orbitofrontal sulcogyral morphology in obsessive–compulsive disorder. (30th April 2019) - Delahoy, Rebekah; Bartholomeusz, Cali F.; Pemberton, Hugh; Alonso, Pino; Pujol, Jesus; Cardoner, Narcis; Menchon, José M.; Soriano-Mas, Carles; Harrison, Ben J.
Highlights: Examination of OFC sulcogyral patterning differences for OCD patients and controls. Occurrence of Type II and III patterning is associated with OCD illness severity. Type I pattern expression is associated with general anxiety in OCD patients. Abstract: Obsessive–compulsive disorder (OCD) has been consistently associated with structural and functional alteration of the orbitofrontal cortex (OFC) and its subcortical connections. In exploring these alterations, a neurodevelopmental basis to OCD has been suggested. While some studies have examined outcomes of early cortical maturation processes, such as global cortical thickness and gyrification, no work has specifically examined the OFC. Within the OFC, three types of sulcogyral patterns have been identified as a result of variance in cortical folding. The distribution of these patterns has been found to differ in patients of various neuropsychiatric disorders relative to the general population, however no study has yet investigated this distribution in individuals with OCD. Eighty OCD patients and 78 healthy controls were evaluated using magnetic resonance imaging, with identification of the sulcogyral pattern based on the method of Chiavaras and Petrides (2000). While gross changes in OFC sulcogyral patterning did not distinguish OCD patients from healthy controls, expression of both the Type II and Type III patterns was significantly associated with increased OCD illness severity. This finding indicates that early neurodevelopmental factors may influence illness severity.